2021
DOI: 10.1002/jper.20-0406
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and serum oxidative stress biomarkers and advanced glycation end products in periodontitis patients with or without diabetes: A cross‐sectional study

Abstract: Background Non‐invasive methods for periodontitis diagnosis would be a clinically important tool. This cross‐sectional study aimed to investigate the association between oxidative stress, glycation, and inflammation markers and periodontal clinical parameters in periodontitis and periodontally healthy patients with type 2 diabetes and corresponding systemically healthy controls. Methods Sixty‐seven periodontally healthy (DM‐H, n = 32) and periodontitis (DM‐P, n = 35) patients with type 2 diabetes, and 54 syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 51 publications
(56 reference statements)
3
47
0
Order By: Relevance
“…Most previous periodontal studies evaluated oxidative stress through the global burden of ROS and guanine-derived biomarkers in saliva and gingival crevicular fluid [42][43][44]. However, in this current study, we evaluated fluctuations in both markers in blood and urine; these fluctuations are more commonly related to systemic oxidative damage markers associated with periodontal diseases, such as MDA and 8-OHdG [13,18,19,[45][46][47][48].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Most previous periodontal studies evaluated oxidative stress through the global burden of ROS and guanine-derived biomarkers in saliva and gingival crevicular fluid [42][43][44]. However, in this current study, we evaluated fluctuations in both markers in blood and urine; these fluctuations are more commonly related to systemic oxidative damage markers associated with periodontal diseases, such as MDA and 8-OHdG [13,18,19,[45][46][47][48].…”
Section: Discussionmentioning
confidence: 94%
“…Several epidemiological studies have reported that periodontitis is related to arteriosclerotic events, and this association has been suggested due to the increase in serum levels of proinflammatory and pro-oxidant markers in both diseases, such as TNFα, IL-1, IL-6, and CRP [26][27][28][29], fibrinogen [30], MDA [18,25], and 8-OHdG [13,31]. Recently, a study has even shown that periodontitis-especially severe-is independently associated with a considerable increase in platelet count due to an increase in the systemic inflammation, which could be a new potential link with cardiovascular disease [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetic patients, salivary RAGE detection has been suggested as a novel biomarker of periodontal health. Serum AGE levels were reported to be elevated in systemically healthy periodontal patients compared to the non-periodontal group, shedding light on the yet not fully known correlation between periodontitis and AGEs [53]. Serum and GCF concentrations of sRAGE were reduced in patients with periodontitis and T2DM compared to those without T2DM.…”
Section: Indirect Effects Of Ages In Periodontal Ligament Cells Mediated Through Receptorsmentioning
confidence: 94%
“…On the same study, TNF-α was controversially elevated, suggesting an antagonistic role of these two molecules and their potential role as valuable biomarkers for high-risk patients [54]. sRAGE levels were found to be downregulated in serum, possibly due to enhanced binding to AGE ligands [53].…”
Section: Indirect Effects Of Ages In Periodontal Ligament Cells Mediated Through Receptorsmentioning
confidence: 94%